Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fneur.2020.00931
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9, Vertebrobasilar Ectasia and Vertebral Artery Dominance in Vertigo or Dizziness Patients With Vascular Risk Factors

Abstract: Background and Purpose: Although vertebrobasilar ectasia (VBE) is diagnosed with increasing frequency, it is not clear whether this is because of altered hemodynamics caused by the effects of matrix metalloproteinases (MMPs) and/or vertebral artery dominance (VAD). Therefore, we investigate the relationship between plasma levels of MMPs and VBE in patients with vertigo or dizziness who also have vascular risk factors, in order to determine whether high levels of MMPs in VBE are independent of VAD. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…The immunohistochemistry in this study showed highly expressed MMP-9 in the arterial wall of mouse IADE, which was consistent with findings of RT-PCR. The MMP-9 expression in murine model was in line with the increased serum level of MMP-9 in patients with dolichoectasia 53 , 54 . The clinical series of vertigo patients revealed that high plasma levels of MMP-9 are associated with vertebrobasilar dolichoectasia 53 .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…The immunohistochemistry in this study showed highly expressed MMP-9 in the arterial wall of mouse IADE, which was consistent with findings of RT-PCR. The MMP-9 expression in murine model was in line with the increased serum level of MMP-9 in patients with dolichoectasia 53 , 54 . The clinical series of vertigo patients revealed that high plasma levels of MMP-9 are associated with vertebrobasilar dolichoectasia 53 .…”
Section: Discussionsupporting
confidence: 63%
“…The MMP-9 expression in murine model was in line with the increased serum level of MMP-9 in patients with dolichoectasia 53 , 54 . The clinical series of vertigo patients revealed that high plasma levels of MMP-9 are associated with vertebrobasilar dolichoectasia 53 . MMP-9 are also elevated in arterial walls of other vascular diseases with inflammatory processes 55 - 61 .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, this degrading process may thin or destroy the internal elastic lamina of arteries ( 14 ). In previous studies, we found that a high level of plasma MMP-9 was associated with basilar arteriectasia in dizziness or vertigo patients ( 15 , 16 ). Experiments on the elastase-induced IADE mouse model demonstrated that arterial wall dilation was characterized by internal elastic lamina rupture, inflammatory cell infiltration, and high expressions of MMP-2 and MMP-9 ( 10 ).…”
Section: Discussionmentioning
confidence: 82%